FITRAH BASED GROUP COUNSELING: A HOLISTIC APPROACH TO ENHANCING STUDENTS' CAREER MATURITY IN THE DIGITAL ERA AND CREATIVE ECONOMY - Rambe, Malim Soleh; Saputri, Nor Mita Ika; Siregar, Azijah Tussolihah (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The advancement of the digital era and the creative economy presents multidimensional challenges in students’ career decision-making. Approximately 68% of high school students in Indonesia experience confusion in determining their career paths due to difficulties in integrating personal potential with contemporary demands. Conventional counseling approaches are considered suboptimal in addressing these needs; therefore, a holistic intervention based on Islamic values is required. Purpose: This study aims to develop and examine the effectiveness of a fitrah-based group counseling model in enhancing students’ career maturity, particularly in aspects of self-understanding, strategic planning, and adaptation to digital transformation. Method: The study employed a quasi-experimental design with a Non-Equivalent Control Group, involving 24 twelfth-grade students of SMA Negeri 8 Padangsidimpuan, divided into an experimental group (12 sessions of fitrah-based counseling) and a control group (conventional counseling). Data were collected using the Career Maturity Inventory and analyzed with the Wilcoxon test. Result: The results revealed a significant improvement in the experimental group (post-test scores 228–288; Z = –3.190, p < 0.001), particularly in the spiritual (79%), creativity (82%), and adaptability (3.2×) dimensions, while the control group showed only marginal progress (scores 159–200). Conclusion: These findings confirm that the fitrah-based counseling model effectively enhances students’ holistic career maturity. The implications include integrating this model into school counseling curricula, developing counselor training modules, and formulating educational policies that combine digital literacy with spiritual values.